Complementary bonding analysis of the N–Si interaction in pentacoordinated silicon compounds using quantum crystallography. Issue 43 (17th October 2019) - Fugel, Malte; Ponomarenko, Maksym V.; Hesse, Maxie F.; Malaspina, Lorraine A.; Kleemiss, Florian; Sugimoto, Kunihisa; Genoni, Alessandro; Röschenthaler, Gerd-Volker; Grabowsky, Simon
Abstract : The unique combination of quantum crystallography and complementary bonding analysis is used to investigate the bonding of pentacoordinated silicon atoms. Abstract : The N–Si interaction in two pentacoordinated silicon compounds is investigated based on a complementary bonding analysis, which consists of bonding descriptors from real space and orbital space. These are derived from X-ray wavefunction refinements of high-resolution X-ray diffraction data of single crystals and from isolated-molecule theoretical wavefunctions. The two pentacoordinated compounds only differ in one methylene group, so that the amino substituent is more flexible in one of the structures, hence probing the attractive or repulsive character of the N–Si interaction. All studies suggest weak dative interactions, which do, however, greatly influence the character of the Si–F bond: A strong N–Si interaction results in a weakened Si–F bond, which is quantified in this study experimentally and theoretically.